2019
DOI: 10.12688/f1000research.17731.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of brain regions associated with working memory deficit in schizophrenia

Abstract: Background: Schizophrenia, a severe psychological disorder, shows symptoms such as hallucinations and delusions. In addition, patients with schizophrenia often exhibit a deficit in working memory which adversely impacts the attentiveness and the behavioral characteristics of a person. Although several clinical efforts have already been made to study working memory deficit in schizophrenia, in this paper, we investigate the applicability of a machine learning approach for identification of the brain regions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In several studies, including a meta‐analysis (Van Snellenberg, Torres, & Thornton, 2006), a region of interest (ROI) analysis was performed specifically for DLPFC and found stronger fMRI response (Karlsgodt et al, 2009; Manoach et al, 2000; Potkin et al, 2009; Van Snellenberg et al, 2016), weaker fMRI response (Fan et al, 2019; Kaminski et al, 2020; Menon, Anagnoson, Mathalon, Glover, & Pfefferbaum, 2001; Pu et al, 2019) or no significant difference in fMRI response (Van Snellenberg et al, 2006) in patients with SZ compared to HC. Additionally, using independent component analysis (ICA), several fMRI studies of WM tasks have revealed significant alterations of fMRI response in patients with SZ relative to HC, which are either correlated or anti‐correlated with WM performance, including stronger fMRI response in bilateral superior frontal gyrus (SFG), PCC, insula, superior temporal gyrus (STG), inferior temporal gyrus, precuneus, parahippocampal gyrus, amygdala, putamen and cerebellum, left DLPFC, cingulate gyrus and inferior parietal lobule (IPL) (Chatterjee et al, 2019; Kim et al, 2009), and weaker fMRI response in bilateral dentate gyrus and cerebellum (Kim et al, 2009). These findings suggest that the aforementioned brain regions may be implicated in the neurobiological mechanisms underlying impairment of WM in SZ (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, including a meta‐analysis (Van Snellenberg, Torres, & Thornton, 2006), a region of interest (ROI) analysis was performed specifically for DLPFC and found stronger fMRI response (Karlsgodt et al, 2009; Manoach et al, 2000; Potkin et al, 2009; Van Snellenberg et al, 2016), weaker fMRI response (Fan et al, 2019; Kaminski et al, 2020; Menon, Anagnoson, Mathalon, Glover, & Pfefferbaum, 2001; Pu et al, 2019) or no significant difference in fMRI response (Van Snellenberg et al, 2006) in patients with SZ compared to HC. Additionally, using independent component analysis (ICA), several fMRI studies of WM tasks have revealed significant alterations of fMRI response in patients with SZ relative to HC, which are either correlated or anti‐correlated with WM performance, including stronger fMRI response in bilateral superior frontal gyrus (SFG), PCC, insula, superior temporal gyrus (STG), inferior temporal gyrus, precuneus, parahippocampal gyrus, amygdala, putamen and cerebellum, left DLPFC, cingulate gyrus and inferior parietal lobule (IPL) (Chatterjee et al, 2019; Kim et al, 2009), and weaker fMRI response in bilateral dentate gyrus and cerebellum (Kim et al, 2009). These findings suggest that the aforementioned brain regions may be implicated in the neurobiological mechanisms underlying impairment of WM in SZ (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI and fMRI) of people with the developing disease in the prodromal phase shows an enlargement of the right inferior frontal gyrus [8,22], that directly correlates with reduced neuronal activity in that region. Changes in brain activity are also observed in regions that include cerebellum, temporal and frontal gyri [23], as well as Heschl's gyrus, which is also reduced in people with schizophrenia [24,25]. There are also functional changes in the region of the insula and amygdala.…”
mentioning
confidence: 97%
“…Besides electrical signals, neural activity produces different signals that can still be used in BCI, such as magnetic and metabolic. The magnetic activity can be recorded with MEG, while metabolic activity can be (as shown in changes in blood flow and blood oxygenation level) monitored with fMRI, Positron Emission Tomography (PET), and optical imaging (Chatterjee et al, 2019). However, these alternative techniques require very sophisticated devices that can only be operated in special facilities, making their use impractical for prototyping and practical implementation (da Silva-Sauer et al, 2016).…”
Section: Brain-computer Interface: Revolution Of Artificial Intelligence In Neurosciencementioning
confidence: 99%